ERK-mediated phosphorylation of Thr735 in TNFα-converting enzyme and its potential role in TACE protein trafficking - Surinder M. Soond; Bethany Everson; David W. H. Riches; Gillian Murphy (2005)
Tumor necrosis factor alpha-converting enzyme (TACE/ADAM17) has been implicated in the inducible shedding of numerous cell surface proteins. In light of this, the regulation of TACE catalytic activation and protein maturation has recently received considerable interest in the context of extracellular signal-regulated kinase activation and the subsequent phosphorylation of TACE at residue Thr735. In this study, we analysed the subcellular localisation of TACE derivatives using laser-scanning confocal microscopy and cell surface biotinylation. Whereas WT.TACE- and T735A.TACE-enhanced green fluorescent protein (-eGFP) fusion derivatives of TACE were both found to localise with the endoplasmic reticulum, a phosphomimicking form of TACE (T735E.TACE-eGFP) was found to colocalise predominantly with components of the protein secretory pathway (COPII vesicles and trans-Golgi network). Additionally, upon analysis of biotinylated ectopic TACE, we observed that inducible trafficking of TACE to the cell surface was dependent upon extracellular signal-regulated kinase activation and phosphorylation of Thr735. We conclude from our observations that phosphorylation of TACE at Thr735 highlights a key step in inducible TACE protein trafficking and maturation.